2015
DOI: 10.1080/14786419.2014.999243
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and biological activities of the genusLinaria(Scrophulariaceae)

Abstract: This is a review on 95 references dealing with the genus Linaria (Scrophularioideae-Antirrhineae tribe), a known genus of the Scrophulariaceae family, which comprises about 200 species mainly distributed in Europe, Asia and North Africa. The use of some Linaria species in folk medicine has attracted the attention for chemical and biological studies. This report is aimed to be a comprehensive overview on the isolated or identified known and often new metabolites from the 41 Linaria species so far cited. It is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Vitexin seemed to be not typical to Linaria species as it was not mentioned to be observed as Linaria species constituent and was also not detected in our experiments. Some other polyphenols reported in the bibliography were identified by reversed-phase HPLC analysis as protocatechuic acid, gallic acid, p-hydroxybenzoic acid, vanillic acid and salicylic acid, caffeic acid, pcoumaric acid, ferulic acid, homoprotocatechuic acid, O-hydroxyphenylacetic acid, gluco-syringic acid and p-methoxybenzoic acid (Cheriet et al, 2015). We were the first to detect also rosmarinic, sinapic and chlorogenic and neochlorogenic acids in L. vulgaris ethanolic extract.…”
Section: Melissa Officinalismentioning
confidence: 70%
“…Vitexin seemed to be not typical to Linaria species as it was not mentioned to be observed as Linaria species constituent and was also not detected in our experiments. Some other polyphenols reported in the bibliography were identified by reversed-phase HPLC analysis as protocatechuic acid, gallic acid, p-hydroxybenzoic acid, vanillic acid and salicylic acid, caffeic acid, pcoumaric acid, ferulic acid, homoprotocatechuic acid, O-hydroxyphenylacetic acid, gluco-syringic acid and p-methoxybenzoic acid (Cheriet et al, 2015). We were the first to detect also rosmarinic, sinapic and chlorogenic and neochlorogenic acids in L. vulgaris ethanolic extract.…”
Section: Melissa Officinalismentioning
confidence: 70%
“…The plant was also used in the treatment of haemorrhoids, scurvy, as a poultice to heal wounds and the infusion of the flowers was used as a diuretic in the Canary Islands. The flowers can be made into a non-permanent yellow dye [64][65][66][67].…”
Section: Linaria Cymbalaria (Syn: Cymbalaria Muralis)mentioning
confidence: 99%
“…The plants belonging to Kickxia genus are well known for the presence of several metabolites such as flavonoids [ 7 , 8 ], alkaloids [ 9 ], terpenoids [ 10 ], and iridoids [ 11 ]. Several traditional uses of Kickxia species around the world have been documented, such as laxatives, diuretics, tonics, anti-diabetic, and antiscorbutic, alongside the treatment of disorders such as hemorrhoids, wounds, and vascular treatments [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plant has yellow flowers, and flowering time extends from February to June [ 13 ]. Kickxia species, including K. aegyptiaca, were documented as significant traditional plants in the treatment of vascular diseases, haemorrhoids, and wounds, along with their uses as laxatives, anti-diabetics, anti-scorbutics, diuretics, and, tonics agents [ 12 , 14 ]. The phytochemical characterization of this plant revealed that it is rich in flavonoids, phenolic acids, glycosides, and iridoids [ 7 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%